K2S2O8-Mediated Arylmethylation of Indoles with Tertiary Amines via sp3 C–H Oxidation in Water - Singh, Manjula; Yadav, Arvind K.; Yadav, Lal Dhar S.; Singh, Rana Krishna Pal (Synlett, 2018)
A transition-metal- and catalyst-free, highly efficient synthesis of 3-arylmethylindoles has been achieved using tertiary amines as both methylene (-CH2-) transfer and arylmethylation agents and K2S2O8 as a convenient oxidant. The key feature of this protocol is the utilisation of K2S2O8 as an inexpensive and easy to handle radical surrogate that can effectively promote the reaction, leading to the formation of C(sp2)–C(sp3)–C(sp2) bonds via sp3 C–H bond oxidation in water at room temperature in a one-pot procedure.
Keywords: alkylation; indoles; tertiary amines; heterocycles; K2S2O8; radical oxidation